THE CORRELATION BETWEEN STUDENTS’ HABIT IN WATCHING ENGLISH MOVIE AND THEIR VOCABULARY MASTERY AT THE ELEVENTH GRADE OF SMKN 02 KOTABUMI ACADEMIC YEAR 2021/2022 - Risky Damayanti; Badawi; Dewi Sartipa; Pebriyantama; Gibran Ahmad Bayudha; Yuin Latifah; Siti Syaadah; Hana Nabila (Universitas Muhammadiyah Kotabumi, 2023)
English is one of the most commonly used as a language of communication of people from different country. Vocabulary is one of the important components in English. Having a lot of vocabulary makes it easier for someone, especially students in the process of learning English. Students who do not have enough vocabulary can difficult to convey or understand the meaning of sentence. The strategy can be done by the teacher or the students themselves. Media is an effective strategy to increase vocabulary, one of the ways is by watching English movie as a habit. This study aimed to determine the correlation between students’ habit watching English movie and their vocabulary mastery at the eleventh grade of SMKN 02 Kotabumi. This research used correlational research. Simple random sampling technique was applied to select the sample. Population of this research was eleventh grade at SMKN 02 Kotabumi which consist of 323 students. The total sample of this research was 48 students. The research instrument used to collect the data were multiple choices test and questionnaire. There are 27 valid items of total multiple choice and questionnaire there are 31 items were valid. Value of reliability in multiple choice rcount was greater than rtable (0,86 > 0,329) and value of reliability in questionnaire rcount was greater than rtable (0,84 > 0,329). In analyzing the data, the researcher was used Pearson Product Moment formula. The result of this research showed that Ha is accepted with the result of hypothesis test rcount is higher than rtable which is 0.483 ˃ 0.284. furthermore, the result of t-test was tcount is higher than ttable which is 3.53 ˃ 2.01, it means that there is significant correlation between students’ habit in watching English movie and their vocabulary mastery at the eleventh grade of SMKN 02 Kotabumi academic year 2021/2022.